Socialization of White Jack Bean Tempe Production as a Strategy to Reduce Stunting Rates in Gumantar Village, North Lombok Regency - Putra, Yudi Pratama; Wrethykandayun, Luh Adhira; Zarleni, Tia; Fitriananda, Fitriananda; Irwandi, Agus Salim; Rahman, Muhamad Abdul; Wulandhari, Liliyan; Sadrian, Yunan; Sukma, Puji Indriani; Apriliana, Dewita; Apriliani, Baiq Dian; Jaya, I Komang Damar (Unram Journal of Community Service, 2024)
Gumantar Village is in North Lombok Regency, West Nusa Tenggara. This village is classified as a developing village with many problems, including stunting. Stunting is caused by mothers and children's lack of adequate nutrition and nutrients, which impacts children's physical and mental growth as the nation's golden generation. Therefore, it is vital to prevent stunting in Gumantar Village, considering the village is the frontline in eradicating stunting. To prevent stunting, the KKN-PMD group of Mataram University initiated the utilization of white Jack bean (Canavalia ensiformis) as a raw material for making tempeh to replace soybeans to increase nutritious food and the economy in Gumantar Village. The activity was carried out from December 2023 to January 2024. This tempeh-making aimed to fulfill the community's nutritional intake through tempeh, which is rich in properties and nutrients and can become a community income to improve the economy. The method used through the work program to reduce stunting rates in Gumantar Village was healthy village socialization on stunting prevention, a stunting campaign through Posyandu, and nutritious food demonstrations to make tempeh from white Jack beans. Other activities carried out to prevent stunting were sexual education to children and socialization of early marriage to adolescents who are experiencing the puberty phase. The results of the socialization activities and demonstrations of processing white Jack beans as a primary ingredient for making tempeh were that the community had a better understanding of how to prevent stunting and how to make tempeh from white Jack beans—most of the community members like the tempeh both in terms of taste, shape, and texture. Participants well accepted sexual education and early marriage socialization.